State managements and poor performance : is this always inevitable? - Robinson-Rickets, Heather ([s.n.] [S.l.], 1991)
Outlines some problems which result in state owned companies not being able to attain high levels of performance and productivity. Reviews the literature in an attempt to highlight some of the problems. Examines some broad issues which have affected the organisational structure and climate of a particular state owned commercial enterprise in the Caribbean.